Induction of Simian Virus 40 Antigen in BSC(1) Transformed Cells - Margalith, Miriam (1970)
Heating to 45 C induced in virus-free clones of simian virus 40 (SV40) transformed BSC(1) cells the synthesis of SV40 viral antigen, as evidenced by immunofluorescence. Up to 3.8% of the cells exhibited viral antigen 72 hr after heating to 45 C for 30 min. Depletion of arginine from the medium of the heated cells enhanced and increased the percentage of cells synthesizing viral antigen to 11%. Cytosine arabinoside completely inhibited the induction of the viral antigen. No infectious virus was recovered from the cells in which synthesis of viral antigen was induced. However, small amounts of infectious SV40 virus were rescued from the BSC(1) transformed cells by fusion with rabbit kidney cells or by treatment with mitomycin C.